Ant colony system with stagnation avoidance for the scheduling of real-time tasks - Yacine, Laalaoui; Habiba, Drias; Adel, Bouridah; R. Badlishah, Ahmad, Prof. Madya Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/